Do Maternal Micronutrient Deficiencies Program the Body Composition and Behavior of the Offspring? Probable Underlying Mechanisms - Kalle, Anand Kumar; Ghosh, Shampa; Thomas, Anju Elizabeth; Manchala, Raghunath (Annals of the National Academy of Medical Sciences (India), 2019)
Obesity and noncommunicable diseases (NCDs) like diabetes are epidemic in India. Developmental origins of health and disease hypothesis, based on epidemiological evidence, associates maternal undernutrition and low birth weight (LBW) of the offspring with increased obesity and diabetes in their later life. Considering widespread maternal micronutrient (MN) deficiencies, LBW, and NCDs in India, we tested the hypothesis, “maternal MN deficiency per se programs the offspring for obesity and increases risk for NCDs in their later life” in rodent models. We showed in Wistar rat offspring that maternal MN (single or combined) deficiency per se: (1) increased body fat (visceral fat) and altered lipid metabolism, (2) decreased lean body and fat free mass, and (3) altered muscle function and altered glucose tolerance/metabolism and insulin sensitivity. Rehabilitation prevented vitamin but not mineral restriction-induced changes in offspring, which showed partial mitigation. Increased oxidative/steroid stress, decreased antioxidant status, and inflammatory state were the associated common mechanisms in the offspring. Our attempts to assess the role of epigenetics showed that folate and/or vitamin B12 deficiencies altered mother’s body composition besides that of the offspring. Additionally, in C57BL/6 mice, B12 deficiency-induced anxiety was observed in mothers and offspring. That expressions of histone modifying enzymes in mice brain and promoter methylation of adiponectin, leptin, and 11βHSD1 genes in rat offspring were altered in MN (B12 and Mg) deficiency suggested that altered epigenetics most likely plays a role in maternal MN deficiency-induced changes in body fat/lipid metabolism and anxiety-like behavior in mothers and offspring.
Keywords: micronutrient restriction; body composition; insulin resistance; lipid and carbohydrate metabolism; oxidative stress; epigenetics